Maturity level and motor coordination performance of teenage badminton players in Malaysia - Hashim, A.; Wazir, M. R.; Fadilah, T. (Asian Journal of Research in Education and Social Sciences, 2023)
The purpose of this study was to determine the level of maturity and motor coordination performance of teenage badminton players in Malaysia. Researchers conducted this cross-sectional study, which involved 102 study samples (male=53, female=49) divided into four age groups (13 years, 14 years, and 15 years). The researcher used a purposive sampling method where the selected sample consisted of the top badminton players from all over Malaysia. The player's maturity level is determined by the method proposed by (Khamis and Roche) to predict adult height using the age of their mother and father. There are six motor coordination performance tests used in this study, namely KTK 'balance beam', KTK 'eye-hand coordination' (EHC), KTK 'jumping sideways' (JS), KTK 'shifting platform' (SP), 'shuttlecock throw' ( ST) and "plate tapping (PT). The findings of this study explain the pattern of increasing maturity levels among male and female badminton players with increasing age. The player's peak maturity level was detected at the age of 15 for boys at a rate of 98.9% or 2.34 cm difference between the mean height of the current and the predicted peak height, while for female players at a rate of 97.79 % or 3.83 cm. Overall, the maturity level of male and female players does not have a significant difference. The KTK test "shifting platform" detected a decrease in performance as the player's age increased. Male players were found to decline by 26 repetitions at the age of 13 to 15 years, while female players by 30 repetitions. The study found that changes in motor coordination performance occurred at different ages for male and female players. In conclusion, the researchers suggest that the management and coaches consider the players' maturity level and motor coordination performance in the player selection process. Coaches are encouraged to include elements of players' maturity levels in the process of designing their training programs. Motor coordination in badminton is seen as important and can be trained to improve game performance.